Does Medullary Versus Cortical Invasion of the Mandible Affect Prognosis in Patients With Oral Squamous Cell Carcinoma? - Li, Chunjie; Lin, Jie; Men, Yi; Yang, Wenbin; Mi, Fanglin; Li, Longjiang (Journal of oral and maxillofacial surgery, 2017)
Whether mandibular involvement by oral squamous cell carcinoma (OSCC) could be identified as a factor for cancer staging and prognosis prediction remains a subject of debate. In addition, the influence of different types of mandibular invasion (cortical or medullary invasion) on patients' prognosis remains unclear. The aim of this systematic review was to establish whether mandibular invasion or its subset should be considered an independent prognostic factor for patients with OSCC. The search for eligible studies was performed according to the predesigned inclusion criteria for a systematic review. Mandibular invasion and invasion depth were considered the primary and secondary predictor variables, respectively. The electronic search was performed using 12 databases. Manual searching covered 14 related journals and references of the included studies were scanned. The risk of bias assessment was evaluated by 2 reviewers using risk-of-bias assessment tools recommended by Saltaji et al (Angle Orthod 82:1115, 2012). Two reviewers extracted the data in duplicate. RevMan 5.2 was used for meta-analysis to assess the primary outcomes (disease-free survival and overall survival) and the secondary outcomes (2- and 5-year survival rate and local control). Eighteen studies (total, 3,756 participants) were included and used as the study sample. Among these included studies, 7 had an unclear risk of bias and the remaining showed a high risk. The results of the meta-analyses showed a significant relation between mandibular invasion and overall survival (P = .04) and, most importantly, that medullary involvement (P = .0001), but not cortical involvement (P = .66), could decrease overall survival. When focusing on disease-specific survival, mandibular medullary involvement predicted a poor disease-specific survival (P < .0001), but cortical involvement showed no effect (P = .66). This review showed that OSCC mandibular medullary invasion, and not mandibular invasion or mandibular cortical invasion, could be an independent prognostic factor for patients.